Characteristics and Outcome of Patients After Allogeneic Hematopoietic Stem Cell Transplantation Treated With Extracorporeal Membrane Oxygenation for Acute Respiratory Distress Syndrome*. Issue 5 (May 2017) - Wohlfarth, Philipp; Beutel, Gernot; Lebiedz, Pia; Stemmler, Hans-Joachim; Staudinger, Thomas; Schmidt, Matthieu; Kochanek, Matthias; Liebregts, Tobias; Taccone, Fabio Silvio; Azoulay, Elie; Demoule, Alexandre; Kluge, Stefan; et al.
Abstract : Objectives: The acute respiratory distress syndrome is a frequent condition following allogeneic hematopoietic stem cell transplantation. Extracorporeal membrane oxygenation may serve as rescue therapy in refractory acute respiratory distress syndrome but has not been assessed in allogeneic hematopoietic stem cell transplantation recipients. Design: Multicenter, retrospective, observational study. Setting: ICUs in 12 European tertiary care centers (Austria, Germany, France, and Belgium). Patients: All allogeneic hematopoietic stem cell transplantation recipients treated with venovenous extracorporeal membrane oxygenation for acute respiratory distress syndrome between 2010 and 2015. Interventions: None. Measurements and Main Results: Thirty-seven patients, nine of whom underwent noninvasive ventilation at the time of extracorporeal membrane oxygenation initiation, were analyzed. ICU admission occurred at a median of 146 (interquartile range, 27–321) days after allogeneic hematopoietic stem cell transplantation. The main reason for acute respiratory distress syndrome was pneumonia in 81% of patients. All but one patient undergoing noninvasive ventilation at extracorporeal membrane oxygenation initiation had to be intubated thereafter. Overall, seven patients (19%) survived to hospital discharge and were alive and in remission of their hematologic disease after a follow-up of 18 (range, 5–30) months. Only one of 24 patients (4%) initiated on extracorporeal membrane oxygenation within 240 days after allogeneic hematopoietic stem cell transplantation survived compared to six of 13 (46%) of those treated thereafter ( p < 0.01). Fourteen patients (38%) experienced bleeding events, of which six (16%) were associated with fatal outcomes. Conclusions: Discouraging survival rates in patients treated early after allogeneic hematopoietic stem cell transplantation do not support the use of extracorporeal membrane oxygenation for acute respiratory distress syndrome in this group. On the contrary, long-term allogeneic hematopoietic stem cell transplantation recipients otherwise eligible for full-code ICU management may be potential candidates for extracorporeal membrane oxygenation therapy in case of severe acute respiratory distress syndrome failing conventional measures. Abstract : Supplemental Digital Content is available in the text.